2017
DOI: 10.1038/nmicrobiol.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for human respiratory syncytial virus NS1-mediated modulation of host responses

Abstract: Human respiratory syncytial virus (hRSV) is a major cause of morbidity and mortality in the pediatric, elderly, and immune compromised populations1,2. A gap in our understanding of hRSV disease pathology is the interplay between virally encoded immune antagonists and host components that limit hRSV replication. hRSV encodes for non-structural (NS) proteins that are important immune antagonists3–6; however, the role of these proteins in viral pathogenesis is incompletely understood. Here we report the crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(89 citation statements)
references
References 60 publications
1
87
1
Order By: Relevance
“…As mentioned, there is very limited conservation of key residues, such as T36, in the NS2 proteins of the two viruses, whose significance is unknown [ 32 ]. Recently determined crystal structure of RSV NS1 showed some similarity of structural fold with the RSV M protein [ 28 ]. The significance of this exclusive similarity at the higher structural level is also enigmatic since the M protein is a virion structural protein that links the genome RNA nucleocapsid to the viral envelope, with no known role in IFN suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, there is very limited conservation of key residues, such as T36, in the NS2 proteins of the two viruses, whose significance is unknown [ 32 ]. Recently determined crystal structure of RSV NS1 showed some similarity of structural fold with the RSV M protein [ 28 ]. The significance of this exclusive similarity at the higher structural level is also enigmatic since the M protein is a virion structural protein that links the genome RNA nucleocapsid to the viral envelope, with no known role in IFN suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the primary structures of the NS proteins show no similarity with any other protein in biology; thus, bioinformatic analysis of their sequences offers no clue to their evolutionary origin or functional domains [ 6 , 9 , 24 ]. Except for the recently solved crystal structure of RSV NS1 [ 28 ], the higher order structure of the pneumoviral NS proteins has also remained unknown, in part due to difficulties of expression of the recombinant proteins; moreover, the crystal structure of RSV NS1 [ 28 ] did not offer any mechanistic insight into its IFN-suppressive function. Nonetheless, we have recently shown that the PVM NS proteins specifically degrade several mouse ISGs, namely IFITM1, TRAFD1 and ISG20 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…NS1 and NS2 have been postulated to have various roles in RSV pathogenesis, generally linked to their anti-IFN activity. In addition to antagonizing type I IFN, NS1, and NS2 may negatively modulate dendritic cell maturation, affect Th17 lymphocyte proliferation, and promote Th2 polarization (35, 98105). Deletion of anti-IFN proteins NS1 and NS2 in RSV live vaccines is responsible for attenuated phenotypes (89).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we uncover insoluble aggregation pathway (NS1Agg) that takes place at salt. This explains the apparent contradiction observed in the lack of effect of residues F17, F56, Y125 in which structure clearly links them to the stabilization of the C-terminal helix, since the thermal denaturation reported therein is in fact insoluble aggregation 12 .…”
Section: Discussionmentioning
confidence: 89%
“…reported by its single and highly sensitive Trp90, preceding the global unfolding transition corresponding to the main ß-sheet core 12 . Although there is no specific protein target defined in therms of binding affinity or structure, this mobile C-terminal helix might have important implications in structure 33 .…”
Section: Discussionmentioning
confidence: 99%